2014
DOI: 10.1177/0898264314529332
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Social Support Among U.S. Chinese Older Adults

Abstract: Chinese older adults perceive a high level of both positive and negative spouse and family support simultaneously. Further longitudinal studies should be conducted to better understand the factors and outcomes associated with perceived positive and negative social support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 47 publications
6
48
0
Order By: Relevance
“…Also, the older men exhibited lower levels of emotional closeness with existing confidants when compared with the women. In general, women are more likely to participate in social activities and community engagement, and, therefore, they have more heterogeneous sources and contacts of network members outside their home [16] . However, this previous work did not specifically include older age groups when gender differences regarding mortality occurred, resulting in more women in widowhood and single households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the older men exhibited lower levels of emotional closeness with existing confidants when compared with the women. In general, women are more likely to participate in social activities and community engagement, and, therefore, they have more heterogeneous sources and contacts of network members outside their home [16] . However, this previous work did not specifically include older age groups when gender differences regarding mortality occurred, resulting in more women in widowhood and single households.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, older adults of Chinese descent -one of the fastest-growing segments of the geriatric population -are faced with disproportionate health burdens, ranging from physical to psychological distress [15] . Although recent studies have begun to examine the dynamic nature of the social relationships of older Chinese immigrants [16] , the social networks of this minority group remain underexplored.…”
mentioning
confidence: 99%
“…Self-reported satisfaction towards social support is a strong predictor of loneliness, [16] and existing literature further reveals that Chinese older immigrants rely on adult children as the most important source of social support. [17,18] Therefore, it is imperative to consider filial piety as an important cultural factor in the investigation of loneliness. A few studies have begun to explore the associations between socio-demographic factors and loneliness, such as marital status, gender, age, education, income, living arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…[35,36] Considering filial piety is often exemplified through behaviors of reciprocity, the psychological effects of receiving filial piety from children can be intensified by immigrating to the U.S., with higher perceived stress in coping with daily life, and lower self-mastery levels to confront with linguistic and cultural barriers. [37,38] While evidence suggested that U.S. Chinese older adults primarily rely on adult children for social support, [18] family-focused social networks are most beneficial to the well-being of older adults. [39,40] Our finding is supported by a study indicating that decreased affection to and from children is associated with higher risk of loneliness among older adults.…”
mentioning
confidence: 99%
“…The second section delves into the PINE study findings on the psychological and social wellbeing of U.S. Chinese older adults, an area which has only received limited attention in population-based aging research (Dong, Chang, Wong, & Simon, 2012a, 2012b. Collectively, these findings showed that contrary to the model minority image, U.S. Chinese older adults were disproportionally affected by psychological and social distress (Chen, Simon, Chang, Zhan, & Dong, 2014;Dong, Chen, Fulmer, & Simon, 2014;Dong, Chen, Wong, & Simon, 2014;Dong, Zhang, Zhang, & Simon, 2014). These results call for further longitudinal studies to examine these older adults' changes in health and well-being of over time to better predict risk and protective factors associated with health disparities among Chinese older adults.…”
mentioning
confidence: 99%